The physical environment quality of the theme hotels in Malaysia: Are guests satisfied? - Asmara, Tengku Nur Afiqah Tengku; Mohi, Zurinawati (School of Tourism, Universitas Ciputra Surabaya, 2024)
Trends in accommodation are a part of the traveler's lifestyle, seeking valuable experiences during their stay. The phenomenon of theme hotels has become a trend in Malaysian accommodation. Unique physical architecture design made a special accommodation in a theme hotel. Physical environment quality is an important attribute that influences guest satisfaction by meeting their needs and expectations. Two primary dimensions, i.e., surrounding indoor and guestroom, were identified for the physical environment quality. Data were obtained from a questionnaire distributed randomly to 400 respondents in five selected theme hotels, and 375 completed questionnaires were returned. However, 360 were appropriate for further analysis. This study was analyzed using Exploratory Factor Analysis and multiple regression analysis. The results show that hotel ambiance and facility aesthetics significantly influence indoor dimensions. The guestroom's cleanliness significantly influenced guest satisfaction with the guestroom dimensions. Findings could assist the management of theme hotels and employees in improving their physical environment quality to ensure guests’ satisfaction. Limitations and future research recommendations are presented.